Ekonomi Politik Media Dalam Industri Musik Digital Spotify - Saputri, Nur Amala (KOMUNIKA, 2021)
Since the emergence of internet media, digital music was born which then marked as a change in the dominance of conventional recorded music. It is slowly and surely replacing the roles of conventional media, starting from the production process, distribution, to the level of music consumption. One of the most prominent music streaming platforms today is Spotify. In practice, the music streaming platform Spotify acts as a cultural industry that seeks to obscure people's real needs. This research uses a qualitative descriptive method based on a critical paradigm. With the aim of analyzing power relations in cultural practices that have been built by the digital music industry, either through the media or by the owners of capital through the perspective of the political economy of communication media. There are 2 main findings as a result of the study. First, there are 5 forms of digital music standardization that emerged because of the Spotify platform. Second, there are 2 forms of culture created from the relationship and identity of digital music actors, namely, the trend of soloist musicians or music by do it yourself, and bargaining power between musicians and music labels. In the end, Spotify is the party who benefits the most because it acts as a mediator who provides services or services for digital music streaming providers.